DESIGN & EVALUATION OF CONTROLLED RELEASE MATRIX TABLETS OF DICLOFENAC SODIUM(BCS CLASS-II DRUG) BY USING NATURAL POLYMERS (International Journal of Food and Nutritional Sciences, 2022)
The objective of this work was to study the effect of various matrixes forming, release retarding and mucoadhesive polymers on the release of BCS class II drugs. Actual aim of this research work was to design and develop an extended-release matrix tablets by using diclofenac sodium (DS). Actual aim of this research work was to design and developed an extended-release matrix tablets by using diclofenac sodium (DS).